2022
DOI: 10.1177/2473011421s00634
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Following Broström Repair with Internalbrace Ligament Augmentation vs Broström Repair Alone for the Treatment of Anterior Talofibular Ligament Injury of the Lateral Ankle

Abstract: Category: Ankle; Sports Introduction/Purpose: The Broström procedure is indicated for lateral ankle instability in the setting of acute or chronic ankle sprains, with injury of the anterior talofibular ligament (ATFL) being the most common. While the procedure is anatomically favorable, one disadvantage of the Broström procedure is significantly reduced strength of the repair when compared with the native ligament. Broström repair with augmentation of an InternalBrace (Arthrex, Naples, FL), nonabsorbable sutur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The most important contribution of this study is that both open and arthroscopic all-inside repair are safe and effective stabilizing techniques for CAI. As reported in previous studies, the improvement of all clinical scores at an average of 5 years follow-up was significant in both OLR and ALR groups [5,20,24,31,39]. In addition, there was no significant difference between the two groups in terms of AOFAS, FAAM-SS scores and risk of complications.…”
Section: Discussionsupporting
confidence: 82%
“…The most important contribution of this study is that both open and arthroscopic all-inside repair are safe and effective stabilizing techniques for CAI. As reported in previous studies, the improvement of all clinical scores at an average of 5 years follow-up was significant in both OLR and ALR groups [5,20,24,31,39]. In addition, there was no significant difference between the two groups in terms of AOFAS, FAAM-SS scores and risk of complications.…”
Section: Discussionsupporting
confidence: 82%
“…The potential benefits of suture tape utilization in ankle ligament reconstruction remain difficult to quantify. Comfort et al 28 retrospectively compared patient-reported outcomes after lateral ligament repair with suture tape augmentation (n = 37) and without it (n = 48). At the median follow-up of 5 years, there was no difference in the Foot and Ankle Ability Measure (FAAM), 12-Item Short-Form Health Survey (SF-12), Tegner Activity Scale, or patient satisfaction between groups.…”
Section: Sportsmentioning
confidence: 99%